2014
DOI: 10.1021/bi5008854
|View full text |Cite
|
Sign up to set email alerts
|

An Oligomeric C-RING Nacre Protein Influences Prenucleation Events and Organizes Mineral Nanoparticles

Abstract: The mollusk shell nacre layer integrates mineral phases with macromolecular components such as intracrystalline proteins. However, the roles performed by intracrystalline proteins in calcium carbonate nucleation and subsequent postnucleation events (e.g., organization of mineral deposits) in the nacre layer are not known. We find that AP7, a nacre intracrystalline C-RING protein, self-assembles to form amorphous protein oligomers and films on mica that further assemble into larger aggregates or phases in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
210
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(226 citation statements)
references
References 58 publications
16
210
0
Order By: Relevance
“…From the morphology of the nanoparticles we speculate that the formed particles were calcite rather than aragonite, vaterite or amorphous calcium carbonate. A similar observation could be made when studying calcium carbonate formation in the presence of proteins where the nacre derived protein AP7 was found to lead to calcium binding and enhanced protein induced local ion concentration [10]. These observations do not exclude a possible role of radiolysis in lowering the pH as has been reported elsewhere [11].…”
Section: Caco3 Formation In Lcstemsupporting
confidence: 71%
See 1 more Smart Citation
“…From the morphology of the nanoparticles we speculate that the formed particles were calcite rather than aragonite, vaterite or amorphous calcium carbonate. A similar observation could be made when studying calcium carbonate formation in the presence of proteins where the nacre derived protein AP7 was found to lead to calcium binding and enhanced protein induced local ion concentration [10]. These observations do not exclude a possible role of radiolysis in lowering the pH as has been reported elsewhere [11].…”
Section: Caco3 Formation In Lcstemsupporting
confidence: 71%
“…The zone width has been found to be of the order of 4-5 µm [10] under standard conditions. These experiments had been performed using atmospheric SEM observing precipitation in a petri dish through a Si x N y membrane in the bottom of the dish with no restriction of dimensions.…”
Section: Discussionmentioning
confidence: 96%
“…These reported studies utilized mole protein quantities, Ca(II) potentiometric methods, and parallel mineralization assay systems to study the early and later events in calcite-based calcium carbonate nucleation and monitor the formation and stabilization of PNCs and ACC in a time-dependent fashion. What was discovered was very informative: these proteins are distinguishable in terms of what mineral species or steps in the non-classical scheme they affect (Figure 4) [58][59][60][61][62][63][64][65][66][67]. Further, using mineralization assays which overlap with the time periods of the potentiometric titrations and utilize similar solution and supersaturation conditions [58][59][60][61][62][63][64][65][66][67] these studies demonstrated that these proteins form hydrogels that can capture, assemble, and organize mineral nanoparticles ( Figure 5) [62,65] consistent with CPA theory [15].…”
Section: Moving Towards More Informative Studiesmentioning
confidence: 97%
“…As an example, recent in vitro studies involving five recombinant mollusk shell nacre-associated proteins [58][59][60][61][62][63][64][65][66] and ACC-stabilizing sea urchin spicule matrix proteins [67,68] have utilized mineralization assay conditions identical to those employed in non-classical nucleation studies [29][30][31][32][33]. What links these different biomineralization proteins together are two common molecular themes [69,70]: intrinsic disorder, or absence of folding protein structure, and amyloid-like aggregation-prone domains, which promote protein-protein association leading to the formation of protein phases or hydrogels [58][59][60][61][62][63][64][65][66][67][68]. These reported studies utilized mole protein quantities, Ca(II) potentiometric methods, and parallel mineralization assay systems to study the early and later events in calcite-based calcium carbonate nucleation and monitor the formation and stabilization of PNCs and ACC in a time-dependent fashion.…”
Section: Moving Towards More Informative Studiesmentioning
confidence: 99%
See 1 more Smart Citation